Transforming dementia care pathway: why shifting to a universal, comprehensive, proactive, local, and integrated model is imperative to improve outcomes - Nair, Pallavi; Junghans, Cornelia; Kay, Michelle; Harris, Matthew; Majeed, Azeem; Hayhoe, Benedict (Frontiers in Dementia, 2026)
Dementia care in the United Kingdom (UK) faces vast and complex systemic challenges, impacting not only individuals with dementia but also their families, communities, and the broader healthcare system. We outline these challenges and advocate for a transformative shift towards proactive and integrated community-anchored models of care. We highlight the UK-based Community Health and Wellbeing Workers (CHWW) model, which already delivers universal, holistic household-level support and is uniquely positioned within the communities to address dementia care gaps. Building on this foundation, we introduce ComPROACT, a CHWW-led outreach approach targeting cognitive decline and dementia across the care continuum. This initiative integrates both pre- and post-diagnostic dementia care support, particularly in underserved communities, not by creating new parallel services but by reimagining existing neighbourhood-based roles. Empowering CHWWs to be dementia-capable offers a sustainable pathway to better bridge the systemic gap between primary care, community, and dementia services.